A Novelistic Querying procedure for clustering the Legal Precedents (International Journal of Engineering and Computer Science, 2017)
In this paper an attempt has been made to propose five query formation methods with professional usage point of view for clustering the dowry crime related legal precedents. K-mean clustering method is used on Tanagra open source for all the methods. The query formation methods are used to generate five types of queries to find the cosine similarity measure between the query Term Frequency Matrix (TFM) and Repository TFM. The repository TFM consists of 500 judgments related to dowry crimes and used in [27]. After the formation of clusters the performance metrics are computed and the results are analyzed in a twofold i) Cluster analysis for within the query formation method ii) Comparison of clustering results of different query formation methods Finally the conclusions and the future scope of the research presented at the end of the paper.